2013
DOI: 10.1074/jbc.m112.437897
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Heat Shock Protein 90α (HSP90α) Induces Nuclear Factor-κB-mediated TCF12 Protein Expression to Down-regulate E-cadherin and to Enhance Colorectal Cancer Cell Migration and Invasion

Abstract: Background: Both secreted HSP90␣ and overexpressed TCF12 enhance colorectal cancer (CRC) cell migration/invasion. Results: Secreted HSP90␣ induces the CD91/IB kinase/NF-B/TCF12 cascade to down-regulate E-cadherin and to enhance CRC cell migration/invasion. Conclusion: Secreted HSP90␣ acts through TCF12 expression to enhance CRC cell spreading. Significance: Secreted HSP90␣ contributes to tumor TCF12 overexpression and can be a therapeutic target of CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 26 publications
(32 reference statements)
3
74
0
Order By: Relevance
“…These results confirmed previous findings indicating that heat shock could alter cell-cell adhesion by down-regulating E-cadherin protein levels (Lang et al, 2012). Recently, Chen, Chen, Chen, Lee, and Huang (2013) demonstrated that the underlying mechanism of E-cadherin expression during thermal stress corresponds with the HSP90-induced TCF-12 gene expression as negative regulator of E-cadherin protein. Moreover, our results clearly indicated that the heat stress-induced mRNA expression, protein derangement and delocalization of E-cadherin could be prevented by GOS pre-treatment.…”
Section: Discussionsupporting
confidence: 90%
“…These results confirmed previous findings indicating that heat shock could alter cell-cell adhesion by down-regulating E-cadherin protein levels (Lang et al, 2012). Recently, Chen, Chen, Chen, Lee, and Huang (2013) demonstrated that the underlying mechanism of E-cadherin expression during thermal stress corresponds with the HSP90-induced TCF-12 gene expression as negative regulator of E-cadherin protein. Moreover, our results clearly indicated that the heat stress-induced mRNA expression, protein derangement and delocalization of E-cadherin could be prevented by GOS pre-treatment.…”
Section: Discussionsupporting
confidence: 90%
“…We demonstrated a unique role for eHsp90 as an initiator of EMT events in cell-based models of prostate cancer (18), thereby providing mechanistic relevancy for its tumorigenic function. Subsequent corroboration of eHsp90 as an EMT inducer in colon cancer (19) lends support for a conserved role for eHsp90 in malignancy. Moreover, several reports have documented elevated Hsp90 in patient serum relative to cancer-free controls (20 -23), implicating a conserved clinical role for eHsp90.…”
mentioning
confidence: 87%
“…Briefly, total cell lysates were prepared by lysing cells in buffer consisting of 10 mM Na 2 HPO 4 , 1.8 mM KH 2 PO 4 , pH 7.4, 137 mM NaCl, 2.7 mM KCl, 0.5% deoxycholate, 1% Nonidet P-40, 0.3% SDS, and 1 mM phenylmethylsulfonyl fluoride (31). Nuclear extracts were prepared according to the protocol provided in the NE-PER TM nuclear and cytoplasmic extraction reagents kit (Pierce) (29). Immunoblot analyses were performed according to the canonical procedure (31).…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of Cell Protein Samples for Immunoblot Analysis-Total cell lysates and nuclear extracts were prepared as described previously (29,31). Briefly, total cell lysates were prepared by lysing cells in buffer consisting of 10 mM Na 2 HPO 4 , 1.8 mM KH 2 PO 4 , pH 7.4, 137 mM NaCl, 2.7 mM KCl, 0.5% deoxycholate, 1% Nonidet P-40, 0.3% SDS, and 1 mM phenylmethylsulfonyl fluoride (31).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation